A meta‐analysis of anatomy laboratory pedagogies. Issue 1 (6th July 2017) - Wilson, Adam B.; Miller, Corinne H.; Klein, Barbie A.; Taylor, Melissa A.; Goodwin, Michael; Boyle, Eve K.; Brown, Kirsten; Hoppe, Chantal; Lazarus, Michelle
Abstract : The debate regarding anatomy laboratory teaching approaches is ongoing and controversial. To date, the literature has yielded only speculative conclusions because of general methodological weaknesses and a lack of summative empirical evidence. Through a meta‐analysis, this study compared the effectiveness of instructional laboratory approaches used in anatomy education to objectively and more conclusively synthesize the existing literature. Studies published between January 1965 and December 2015 were searched through five databases. Titles and abstracts of the retrieved records were screened using eligibility criteria to determine their appropriateness for study inclusion. Only numerical data were extracted for analysis. A summary effect size was estimated to determine the effects of laboratory pedagogies on learner performance and perceptions data were compiled to provide additional context. Of the 3, 035 records screened, 327 underwent full‐text review. Twenty‐seven studies, comprising a total of 7, 731 participants, were included in the analysis. The meta‐analysis detected no effect (standardized mean difference = −0.03; 95% CI = −0.16 to 0.10; P = 0.62) on learner performance. Additionally, a moderator analysis detected no effects ( P ≥ 0.16) for study design, learner population, intervention length, or specimen type. Across studies, student performance on knowledge examinations was equivalent regardless of being exposed to either dissection or another laboratory instructional strategy. This was true of every comparison investigated (i.e., dissection vs. prosection, dissection vs. digital media, dissection vs. models/modeling, and dissection vs. hybrid). In the context of short‐term knowledge gains alone, dissection is no better, and no worse, than alternative instructional modalities. Clin. Anat. 31:122–133, 2018. © 2017 Wiley Periodicals, Inc.